KAJIAN YURIDIS PERPANJANGAN JABATAN PRESIDEN DI INDONESIA - Dewi Pika Lbn Batu (Gapenas Publisher, 2022)
The issue of the extension of the term of position of Joko Widodo as President has caused a polemic in the community. The existence of pro community groups through declaring their wishes in various cities in Indonesia to do change of rules. The demands of course based on the results of the work leadership president by Joko Widodo which is felt by the community to be quite real and the realization of government performance is in the interest of the community. However, this is certainly not agreed upon by various parties and opposes the opinion of extending the term of position of the president by the opposing groups. The extension of the term of position of the president is considered a setback for democracy, violates the 1945 Constitution (UUD 1945), is unconstitutional and injures the 1998 Reformation struggle. In other that, Author interested to do research uses a qualitative method in collecting and managing research data. The data that has been obtained by the Author is analyzed and summarized in descriptive form